Characterisation of the Antarctic stratospheric vortex mixing barrier - Cameron, Christopher (11809400) (2019)
The strongest stratospheric circulation in the Southern Hemisphere is the Antarctic Circumpolar Vortex (ACV) which forms each winter and spring as a zone of westerly winds surrounding Antarctica, presenting a barrier to transport of air masses between middle and high-latitudes. This barrier contributes to stratospheric temperatures above the polar region dropping sufficiently low in spring to allow for the processes leading to ozone destruction. Unfortunately, the ACV is generally not well simulated in Global Climate Models (GCMs), and this presents a challenge for model accuracy and projections in the face of a changing climate and a recovering ozone hole. In this research, an assessment is made of the performance of a range of mixing metrics in representing the ACV based on reanalyses, including: Effective Diffusivity, Contour Crossing, the Lagrangian function $M$, and Meridional Impermeability. It is shown that Meridional Impermeability -- which provides a measure of the strength of the meridional mixing barrier as a function of potential vorticity (PV) gradient and wind-speed -- acts as a useful proxy for more complex metrics. In addition, Meridional Impermeability displays a well-defined vortex profile across equivalent latitude, which is not seen to the same degree in the other metrics assessed. Representation of the ACV is further compared between climate models and reanalyses based on Meridional Impermeability. It is shown that while climate models have improved in their representation of the vortex barrier over time, there are still significant discrepancies between models and reanalyses. One cause of these discrepancies may result from the use of prescribed ozone fields rather than interactive ozone chemistry. This is further examined by comparing Chemistry Climate Model (CCM) simulations using interactive ozone chemistry, with those using prescribed ozone at either 3-D (i.e., height, latitude and longitude) or 2-D (i.e., height, latitude) dimensionality. Considerable improvement in the representation of the ACV can be achieved by shifting from 2-D to 3-D prescribed ozone fields, and interactive ozone chemistry further improves its representation. However, discrepancies in model representation of the ACV still remain. Previous researchers have also attributed discrepancies in model representation of the polar vortices to the model resolution, and the parameterization of gravity waves at the sub-grid scale -- these factors are considered to contribute to the discrepancies found in simulations undertaken here also. The results of this research are expected to provide guidance to improve the representation of vortex processes in climate modelling.